Heating material for PTC heating bag of new energy automobile and preparation process of heating material
Magnetic liquid metal carbon nanotubes are prepared by composited carboxylated multi-walled carbon nanotubes, iron ions and gallium indium alloys, and using carbon nanotube composite hydrogel fiber and nanofluid technology, the thermal stability and comfort of automotive PTC heating materials during long-term heating and deformation are solved, and a heating material with high conductivity and high electrothermal performance is achieved.
Patent Information
- Application Number
- CN202411896520.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-14
AI Technical Summary
The existing automotive PTC heating pack heating materials are prone to deterioration and deformation when heated for a long time and under human pressure, resulting in a decrease in thermal stability and a decrease in comfort.
Magnetic liquid metal carbon nanotubes are prepared by composite carboxylated multi-walled carbon nanotubes, iron ions and gallium indium alloys, and uniformly coated on the surface of polyester fabrics through carbon nanotube composite hydrogel fibers and nanofluid technology to form heat generating materials with high conductivity and high electrothermal properties.
It improves the thermal stability and flexibility of the heating material, extends the service life, and ensures that good electric heating performance and electrical conductivity can be maintained under long-term heating and deformation.
Smart Images

Figure CN119615637A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heating materials, and in particular to a heating material for a PTC heating pack of a new energy vehicle and a preparation process thereof. Background Art
[0002] The automotive PTC heating pack is a commonly used automotive heating device that uses the characteristics of positive temperature coefficient (PTC) materials to provide safe and efficient heating effects. The resistance of the PTC material increases with the increase in temperature, which enables it to automatically adjust the power during the heating process to avoid overheating, thereby ensuring safety and reliability. The PTC heating pack is often used for heating seats and steering wheels, defrosting rearview mirrors, and preheating oil circuits. Therefore, a layer of leather or isolation material will be wrapped on the surface of the PTC heating pack to control the temperature emitted by the PTC heating material so that it can be used in different in-car scenarios.
[0003] However, when PTC heating packs are used in car seats and steering wheels, since the human body will not stay still when sitting in the seat, the heating material of the PTC heating pack used in the seat will often deform while heating. Long-term heating can easily lead to degradation and deformation of the heating material, and this phenomenon is more obvious when subjected to human body pressure. Material degradation will also lead to reduced thermal stability, that is, it is impossible to increase the resistance to control the temperature to remain unchanged as the temperature rises. As the thermal stability decreases, the temperature of the heating material will further rise. Higher temperatures will aggravate the degradation of the heating material, resulting in irreversible deformation of the heating material and inability to deform when the human body sits down, thereby reducing the comfort of use.
[0004] Therefore, the present invention provides a heating material for a PTC heating pack of a new energy vehicle and a preparation process thereof to solve the above problems. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a heating material for a PTC heating pack of a new energy vehicle and a preparation process thereof.
[0006] A preparation process of a heating material for a PTC heating pack of a new energy vehicle comprises the following steps: S1: Preparation of magnetic liquid metal carbon nanotubes The carboxylated multi-walled carbon nanotubes, FeCl3 solution and FeCl2 solution are mixed in a reaction bottle, heated to obtain a hot solution, sodium citrate aqueous solution is added dropwise to the hot solution, and allowed to stand for reaction to obtain an iron-compounded carbon nanotube suspension, the iron-compounded carbon nanotube suspension and gallium-indium alloy are mixed, ultrasonically treated to obtain a treated suspension, the treated suspension is allowed to stand, and magnetically separated to obtain magnetic liquid metal carbon nanotubes; S2: Preparation of carbon nanotube composite hydrogel fibers Add salicylic acid and acrylamide to deionized water, stir, then add crosslinking agent MBA, catalyst TEMED and initiator APS to obtain a mixed solution, add magnetic liquid metal carbon nanotubes to the mixed solution, polymerize, and obtain carbon nanotube composite hydrogel fibers; S3: Preparation of carbon nanotube composite nanofluids Weighing deionized water, heating, and magnetically stirring, adding carbon nanotube composite hydrogel fibers to the deionized water during magnetic stirring, and then adding graphene and anionic surfactant thereto to obtain a carbon nanotube composite nanofluid; S4: Preparation of heating materials for PTC heating packs in new energy vehicles Polyester fabric is selected as the base fabric, acrylic emulsion is evenly coated on the surface of the polyester fabric, and then dried. Then, carbon nanotube composite nanofluid is coated on the surface and dried to obtain a heating material for a PTC heating pack of a new energy vehicle.
[0007] Furthermore, step S1 of preparing magnetic liquid metal carbon nanotubes comprises the following steps: S1.1: 0.5-1 parts by mass of carboxylated multi-walled carbon nanotubes, 6-10 parts by volume of 0.1M FeCl3 solution and 3-6 parts by volume of 0.05M FeCl2 solution are mixed in a reaction flask, and then 5-10% by mass of ammonia water is added dropwise to the reaction flask until the pH value in the reaction flask is 8-9, heated to 80-85°C, and stirred for reaction for 30-35 minutes to obtain a hot solution; S1.2: Add 2-5 parts by volume of sodium citrate aqueous solution dropwise to the hot solution, maintain the reaction temperature at 60-65° C., and allow the reaction to stand for 1.5-2 hours to obtain an iron-complexed carbon nanotube suspension; S1.3: 0.02-0.04 parts by weight of the iron-compounded carbon nanotube suspension and 0.1-0.2 parts by weight of the gallium-indium alloy are mixed, and then cooled to 0-4° C. in an ice water bath, and subjected to ultrasonic treatment for 5-10 minutes to obtain a treated suspension; S1.4: The treated suspension is allowed to stand at 24-26°C, separated by magnetic attraction, the separated precipitate is dialyzed, washed with distilled water and anhydrous ethanol three times respectively, and vacuum dried to obtain magnetic liquid metal carbon nanotubes.
[0008] Furthermore, step S2 of preparing carbon nanotube composite hydrogel fibers comprises the following steps: S2.1: Add 0.4-0.5 parts by mass of salicylic acid and 3.6-4 parts by mass of acrylamide to 15-20 parts by mass of deionized water, stir magnetically for 1-1.5 hours, and after dissolution, add 1-2 parts by mass of crosslinker MBA, 0.5-1 parts by mass of catalyst TEMED and 2-3 parts by mass of initiator APS, stir at 800-1000 r / min for 10-20 minutes to obtain a mixed solution; S2.2: Add magnetic liquid metal carbon nanotubes to the mixed solution, the material-liquid ratio of magnetic liquid metal carbon nanotubes to the mixed solution is 1g: (0.5-0.8)L, and obtain a suspension. Inject the suspension into a polytetrafluoroethylene mold, polymerize at 24-26℃ for 6-7h, then take out and dry to obtain carbon nanotube composite hydrogel fibers.
[0009] Furthermore, step S3 of preparing carbon nanotube composite nanofluid comprises the following steps: S3.1: Weigh 10-15 parts by weight of deionized water, heat to 60-70° C., and magnetically stir for 20-30 minutes. During the magnetic stirring, add 5-8 parts by weight of carbon nanotube composite hydrogel fibers to the deionized water; S3.2: Add 6-10 parts by mass of graphene and 1-3 parts by mass of anionic surfactant thereto, and stir for 5-10 minutes to obtain a carbon nanotube composite nanofluid.
[0010] Furthermore, step S4 prepares the heating material for the PTC heating pack of the new energy vehicle, comprising the following steps: S4.1: Select a 20cm×20cm polyester fabric as the base fabric, insert the wire into the fabric in a spiral manner, and evenly coat the surface of the polyester fabric with 16-24uL / cm2 of acrylic emulsion, and dry it at 125-130℃ for 5-10min; S4.2: Then, 0.04-0.06 g / cm2 of carbon nanotube composite nanofluid is coated on the surface and dried at 40-50°C to obtain the heating material for the PTC heating pack of new energy vehicles.
[0011] Furthermore, in step S1.3, the mass proportion of gallium metal in the gallium-indium alloy is 75%, and the mass proportion of indium metal is 25%.
[0012] Furthermore, the anionic surfactant in step S3.2 is specifically sodium dodecyl sulfate.
[0013] A heating material for a PTC heating pack of a new energy vehicle is prepared by the above-mentioned preparation process of a heating material for a PTC heating pack of a new energy vehicle.
[0014] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention prepares magnetic liquid metal carbon nanotubes by compounding carboxylated multi-walled carbon nanotubes, iron ions and gallium-indium alloys. Multi-walled carbon nanotubes are used as carriers, and iron ion and ferrous ion solutions are first converted into ferrites. Then, magnetic ferrite particles are uniformly dispersed on the surface of the multi-walled carbon nanotubes, and the gallium-indium alloy is filled and dispersed inside the carbon nanotubes to form a microstructure of ferrite particles and multi-walled carbon nanotubes mixed with gallium-indium alloys. Such a structure can protect the gallium-indium alloy from corrosion and oxidation by the multi-walled carbon nanotube coating. In addition, the gallium-indium alloy as the core can have higher electrical conductivity and electrothermal performance, and the ferrite particles mixed with the multi-walled carbon nanotubes can improve the magnetic properties of the material, thereby having high electrical conductivity. The good electrothermal performance brought by the high electrical conductivity makes the heating material for PTC heating packs prepared by the heating material have excellent and stable electrothermal performance, and is durable and has a longer service life.
[0015] 2. The present invention prepares carbon nanotube composite hydrogel fibers by mixing magnetic liquid metal carbon nanotubes with a mixed solution with salicylic acid and acrylamide as main raw materials. The liquid properties of the liquid metal gallium indium alloy enable it to combine with salicylic acid to form a gel, and then form a hydrogel form through the emulsification effect of acrylamide, thereby improving the water absorption and water retention properties of the heating material prepared with the carbon nanotube composite hydrogel fiber as the main material, thereby ensuring the dryness of the external environment, thereby preventing the energized part of the heating material from triggering power outages due to a humid environment, and at the same time being more tough and durable, and not easy to break when subjected to external force, so that when the prepared heating material for the PTC heating pack responds to temperature through electric current, there will be no material degradation, and it still has good thermal stability and flexibility when used for a long time, and is not easily damaged during repeated use.
[0016] 3. The present invention prepares a carbon nanotube composite nanofluid by adding graphene and a surfactant to the carbon nanotube composite hydrogel fiber, and adheres it to the surface of the polyester fabric through an acrylic emulsion. The composite nanofluid prepared by introducing graphene greatly improves the fluidity of the carbon nanotube, so that the carbon nanotube loaded with gallium-indium alloy can be inserted into the gap of the polyester fabric through the fluidity of the nanofluid, and the viscosity between the gallium-indium alloy and the graphene is increased by the acrylic emulsion, and the weather resistance of the carbon nanotube composite nanofluid is improved, thereby ensuring that the heating material with carbon nanotubes as the main raw material can be evenly distributed on the polyester fabric to perform uniform heating. At the same time, polyester has good flexibility. The carbon nanotube composite nanofluid is bonded to the surface of the polyester fabric through acrylic emulsion, which will not affect the flexibility of the polyester fabric. This allows the heating material to still maintain good performance when bent and folded, and at the same time it also has the high conductivity and electrothermal properties of carbon nanotubes. The automotive PTC heating pack made of this material can be used for seats and steering wheels. When the seats are in use, they will be deformed under pressure. This material can maintain good conductivity and thermal stability when bent and folded, and even if it is deformed under force for a long time, it will not be unstable, and the product is more durable and stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0018] Figure 1 This is a flow chart of the preparation process of the heating material for the PTC heating pack of new energy vehicles used in the embodiment of the present invention. DETAILED DESCRIPTION
[0019] The following is a detailed description of a heating material for a PTC heating pack of a new energy vehicle and its preparation process provided by the present invention in combination with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention. Example 1
[0020] A preparation process of heating material for PTC heating pack of new energy vehicle, such as Figure 1 As shown, the following steps are included: S1: Preparation of magnetic liquid metal carbon nanotubes S1.1: 0.5 parts by mass of carboxylated multi-walled carbon nanotubes, 6 parts by volume of 0.1M FeCl3 solution and 3 parts by volume of 0.05M FeCl2 solution were mixed in a reaction flask, and then 5% by mass of ammonia water was added dropwise to the reaction flask until the pH value in the reaction flask reached 8, and the mixture was heated to 80°C and stirred for 30 minutes to obtain a hot solution; S1.2: Add 2 parts by volume of sodium citrate aqueous solution dropwise to the hot solution, maintain the reaction temperature at 60°C, and allow to react for 1.5 hours to obtain an iron-complexed carbon nanotube suspension; S1.3: 0.02 parts by mass of the iron-compounded carbon nanotube suspension and 0.1 parts by mass of the gallium-indium alloy are mixed, wherein the gallium metal accounts for 75% by mass and the indium metal accounts for 25% by mass, and then cooled to 0° C. in an ice-water bath, and subjected to ultrasonic treatment for 5 minutes to obtain a treated suspension; S1.4: The treated suspension is allowed to stand at 24°C, separated by magnetic attraction, the separated precipitate is dialyzed, washed with distilled water and anhydrous ethanol three times respectively, and vacuum dried to obtain magnetic liquid metal carbon nanotubes.
[0021] S2: Preparation of carbon nanotube composite hydrogel fibers S2.1: Add 0.4 parts by mass of salicylic acid and 3.6 parts by mass of acrylamide to 15 parts by mass of deionized water, stir magnetically for 1 hour, and then add 1 part by mass of crosslinker MBA, 0.5 parts by mass of catalyst TEMED and 2 parts by mass of initiator APS after dissolution, and stir at 800 r / min for 10 minutes to obtain a mixed solution; S2.2: Add magnetic liquid metal carbon nanotubes to the mixed solution with a solid-liquid ratio of 1g:0.5L to obtain a suspension, inject the suspension into a polytetrafluoroethylene mold, polymerize at 24°C for 6h, then take out and dry to obtain carbon nanotube composite hydrogel fibers.
[0022] S3: Preparation of carbon nanotube composite nanofluids S3.1: Weigh 10 parts by weight of deionized water, heat to 60°C, and magnetically stir for 20 minutes. During the magnetic stirring, add 5 parts by weight of carbon nanotube composite hydrogel fibers to the deionized water; S3.2: 6 parts by mass of graphene and 1 part by mass of anionic surfactant sodium dodecyl sulfate are added thereto, and stirred for 5 minutes to obtain a carbon nanotube composite nanofluid.
[0023] S4: Preparation of heating materials for PTC heating packs in new energy vehicles S4.1: Select a 20 cm × 20 cm polyester fabric as the base fabric, insert the wire into the fabric in a spiral manner, and evenly coat the surface of the polyester fabric with 16 uL / cm2 of acrylic emulsion, and dry it at 125°C for 5 minutes; S4.2: Then, 0.04 g / cm2 of carbon nanotube composite nanofluid is coated on the surface and dried at 40°C to obtain the heating material for the PTC heating pack of new energy vehicles. Example 2
[0024] A preparation process of heating material for PTC heating pack of new energy vehicle, such as Figure 1 As shown, the following steps are included: S1: Preparation of magnetic liquid metal carbon nanotubes S1.1: 1 part by mass of carboxylated multi-walled carbon nanotubes, 10 parts by volume of 0.1M FeCl3 solution and 6 parts by volume of 0.05M FeCl2 solution were mixed in a reaction flask, and then 5% by mass of ammonia water was added dropwise to the reaction flask until the pH value in the reaction flask reached 8, and the mixture was heated to 80°C and stirred for 30 minutes to obtain a hot solution; S1.2: Add 5 parts by volume of sodium citrate aqueous solution dropwise to the hot solution, maintain the reaction temperature at 60° C., and allow the reaction to stand for 1.5 hours to obtain an iron-complexed carbon nanotube suspension; S1.3: 0.04 parts by mass of the iron-compounded carbon nanotube suspension and 0.2 parts by mass of the gallium-indium alloy are mixed, wherein the gallium metal accounts for 75% by mass and the indium metal accounts for 25% by mass of the gallium-indium alloy, and then cooled to 0° C. in an ice-water bath, and subjected to ultrasonic treatment for 5 minutes to obtain a treated suspension; S1.4: The treated suspension is allowed to stand at 24°C, separated by magnetic attraction, the separated precipitate is dialyzed, washed with distilled water and anhydrous ethanol three times respectively, and vacuum dried to obtain magnetic liquid metal carbon nanotubes.
[0025] S2: Preparation of carbon nanotube composite hydrogel fibers S2.1: Add 0.5 parts by mass of salicylic acid and 4 parts by mass of acrylamide to 20 parts by mass of deionized water, stir magnetically for 1 hour, and then add 2 parts by mass of crosslinker MBA, 1 part by mass of catalyst TEMED and 3 parts by mass of initiator APS after dissolution, and stir at 800 r / min for 10 minutes to obtain a mixed solution; S2.2: Add magnetic liquid metal carbon nanotubes to the mixed solution with a solid-liquid ratio of 1g:0.8L to obtain a suspension, inject the suspension into a polytetrafluoroethylene mold, polymerize at 24°C for 6h, then take out and dry to obtain carbon nanotube composite hydrogel fibers.
[0026] S3: Preparation of carbon nanotube composite nanofluids S3.1: Weigh 15 parts by weight of deionized water, heat to 60°C, and magnetically stir for 20 minutes. During the magnetic stirring, add 8 parts by weight of carbon nanotube composite hydrogel fibers to the deionized water; S3.2: 10 parts by mass of graphene and 3 parts by mass of anionic surfactant sodium dodecyl sulfate are added thereto, and the mixture is stirred for 5 minutes to obtain a carbon nanotube composite nanofluid.
[0027] S4: Preparation of heating materials for PTC heating packs in new energy vehicles S4.1: Select a 20cm×20cm polyester fabric as the base fabric, insert the wire into the fabric in a spiral manner, and evenly coat the surface of the polyester fabric with 24uL / cm2 of acrylic emulsion, and dry it at 125℃ for 5min; S4.2: Then, 0.06 g / cm2 of carbon nanotube composite nanofluid is coated on the surface and dried at 40°C to obtain the heating material for the PTC heating pack of new energy vehicles. Example 3
[0028] A preparation process of heating material for PTC heating pack of new energy vehicle, such as Figure 1 As shown, the following steps are included: S1: Preparation of magnetic liquid metal carbon nanotubes S1.1: 0.5 parts by mass of carboxylated multi-walled carbon nanotubes, 6 parts by volume of 0.1M FeCl3 solution and 3 parts by volume of 0.05M FeCl2 solution were mixed in a reaction flask, and then 5% by mass of ammonia water was added dropwise to the reaction flask until the pH value in the reaction flask reached 9, and the mixture was heated to 85°C and stirred for 35 minutes to obtain a hot solution; S1.2: Add 2 parts by volume of sodium citrate aqueous solution dropwise to the hot solution, maintain the reaction temperature at 65°C, and allow to react for 2 hours to obtain an iron-complexed carbon nanotube suspension; S1.3: 0.02 parts by mass of the iron-compounded carbon nanotube suspension and 0.1 parts by mass of the gallium-indium alloy are mixed, wherein the gallium metal accounts for 75% by mass and the indium metal accounts for 25% by mass, and then cooled to 4° C. in an ice water bath, and subjected to ultrasonic treatment for 10 minutes to obtain a treated suspension; S1.4: The treated suspension is allowed to stand at 26°C, separated by magnetic attraction, the separated precipitate is dialyzed, washed with distilled water and anhydrous ethanol three times respectively, and vacuum dried to obtain magnetic liquid metal carbon nanotubes.
[0029] S2: Preparation of carbon nanotube composite hydrogel fibers S2.1: Add 0.4 parts by mass of salicylic acid and 3.6 parts by mass of acrylamide to 15 parts by mass of deionized water, stir magnetically for 1.5 hours, and after dissolution, add 1 part by mass of crosslinker MBA, 0.5 part by mass of catalyst TEMED and 2 parts by mass of initiator APS, and stir at 1000 r / min for 20 minutes to obtain a mixed solution; S2.2: Add magnetic liquid metal carbon nanotubes to the mixed solution with a solid-liquid ratio of 1g:0.5L to obtain a suspension, inject the suspension into a polytetrafluoroethylene mold, polymerize at 26°C for 7h, then take out and dry to obtain carbon nanotube composite hydrogel fibers.
[0030] S3: Preparation of carbon nanotube composite nanofluids S3.1: Weigh 10 parts by weight of deionized water, heat to 70°C, and magnetically stir for 30 minutes. During the magnetic stirring, add 5 parts by weight of carbon nanotube composite hydrogel fibers to the deionized water; S3.2: 6 parts by mass of graphene and 1 part by mass of anionic surfactant sodium dodecyl sulfate are added thereto, and the mixture is stirred for 10 minutes to obtain a carbon nanotube composite nanofluid.
[0031] S4: Preparation of heating materials for PTC heating packs in new energy vehicles S4.1: Select a 20cm×20cm polyester fabric as the base fabric, insert the wire into the fabric in a spiral manner, and evenly coat the surface of the polyester fabric with 16uL / cm2 of acrylic emulsion, and dry it at 130℃ for 10min; S4.2: Then, 0.04 g / cm2 of carbon nanotube composite nanofluid is coated on the surface and dried at 50°C to obtain the heating material for the PTC heating pack of new energy vehicles.
[0032] Comparative Example 1: Comparative Example 1 is the heating material in the contents of a commercially available automotive PTC heating pack.
[0033] Comparative Example 2: Compared with Example 1, the difference of Comparative Example 2 is that no FeCl3 solution and FeCl2 solution are added in step S1.1, specifically: "S1.1: add 0.5 parts by mass of carboxylated multi-walled carbon nanotubes to a reaction bottle, and then add 5% by mass fraction of ammonia water to the reaction bottle until the pH value in the reaction bottle is 8, heat to 80°C, stir the reaction for 30 minutes, and obtain a hot solution;" and the other steps remain unchanged. The prepared heating material for new energy vehicle PTC heating pack is recorded as Comparative Example 2.
[0034] Comparative Example 3: Compared with Example 1, the difference of Comparative Example 3 is that no gallium-indium alloy is added in step S1.3, specifically: "S1.3: Cool 0.02 mass parts of iron-compounded carbon nanotube suspension to 0°C in an ice-water bath, and ultrasonically treat for 5 minutes to obtain a treated suspension", and the other steps remain unchanged. The prepared heating material for new energy vehicle PTC heating pack is recorded as Comparative Example 3.
[0035] Comparative Example 4: Compared with Example 1, the difference of Comparative Example 4 is that salicylic acid is not added in step S2.1, specifically: "S2.1: add 3.6 parts by mass of acrylamide to 15 parts by mass of deionized water, stir magnetically for 1 hour, add 1 part by mass of cross-linking agent MBA, 0.5 parts by mass of catalyst TEMED and 2 parts by mass of initiator APS after dissolution, stir at 800r / min for 10 minutes to obtain a mixed solution", and the other steps remain unchanged, and the prepared heating material for new energy vehicle PTC heating pack is recorded as Comparative Example 4.
[0036] Comparative Example 5: Compared with Example 1, the difference of Comparative Example 5 is that no acrylamide is added in step S2.1, specifically: "S2.1: add 0.4 parts by mass of salicylic acid to 15 parts by mass of deionized water, stir magnetically for 1 hour, add 1 part by mass of cross-linking agent MBA, 0.5 parts by mass of catalyst TEMED and 2 parts by mass of initiator APS after dissolution, stir at 800r / min for 10 minutes to obtain a mixed solution", and the other steps remain unchanged. The prepared heating material for new energy vehicle PTC heating pack is recorded as Comparative Example 5.
[0037] Comparative Example 6: Compared with Example 1, the difference of Comparative Example 6 is that step S4.1 is not performed, and step S4.2 is directly performed to coat the carbon nanotube composite nanofluid on the surface of the polyester fabric, specifically: "S4: Preparation of heating material for PTC heating pack of new energy vehicle S4.1: Select a 20 cm × 20 cm polyester fabric as the base fabric, insert the wire into the fabric in a threaded manner, and coat 0.04 g / cm2 of carbon nanotube composite nanofluid on the surface of the polyester fabric, and dry it at 40°C to obtain a heating material for a PTC heating pack for a new energy vehicle. The remaining steps remain unchanged, and the prepared heating material for a PTC heating pack for a new energy vehicle is recorded as Comparative Example 6.
[0038] Comparative Example 7: Compared with Example 1, the difference of Comparative Example 7 is that the polyester fabric in step S4.1 is replaced by a PET film, and the acrylic emulsion and the carbon nanotube composite nanofluid are coated on the PET film, specifically: "S4: Preparation of heating material for PTC heating pack of new energy vehicle S4.1: Select a 20 cm × 20 cm PET film as the base film, evenly coat the surface of the PET film with 16 uL / cm2 of acrylic emulsion, and dry at 125°C for 5 min; S4.2: Then, 0.04 g / cm2 of carbon nanotube composite nanofluid is coated on the surface, and dried at 40°C to obtain a heating material for a PTC heating pack for a new energy vehicle. The remaining steps remain unchanged, and the prepared heating material for a PTC heating pack for a new energy vehicle is recorded as Comparative Example 7.
[0039] Take Examples 1-3 and Comparative Examples 1-7, use five 34cm*0.8cm copper foils as conductors, and place the copper foils as cut-off strips at both ends of Examples 1-3 and Comparative Examples 1-7, with a spacing of 5cm. Connect the two cut copper foil strips to a power source and power on. Use a thermocouple temperature monitor to test the surface temperature of Examples 1-3 and Comparative Examples 1-7, and use a deformation tester to calculate whether there is deformation in Examples 1-3 and Comparative Examples 1-7 before and after 24 hours of continuous heating, as shown in Tables 1 and 2.
[0040] Table 1: Surface temperature (unit: °C) 2h 4h 6h 8h Example 1 221.3 224.6 226.1 227.4 Example 2 220.6 225.5 226.8 227.6 Example 3 221.9 224.3 226.7 227.8 Comparative Example 1 200.5 206.9 214.6 224.1 Comparative Example 2 180.6 185.4 192.6 212.5 Comparative Example 3 163.6 167.5 175.6 192.4 Comparative Example 4 207.6 211.4 214.9 215.6 Comparative Example 5 207.7 209.4 213.4 216.2 Comparative Example 6 211.5 217.4 229.6 244.9 Comparative Example 7 203.2 217.8 230.9 245.3 Table 2: 24h continuous fever morphology Continuous fever for 24 hours Example 1 No deformation Example 2 No deformation Example 3 No deformation Comparative Example 1 Deformation 5% Comparative Example 2 Deformation 2% Comparative Example 3 Deformation 8% Comparative Example 4 Deformation 7% Comparative Example 5 Deformation 2% Comparative Example 6 Deformation 15% Comparative Example 7 Deformation 18% Embodiments 1-3 did not deform after continuous heating for 24 hours, and the surface temperature of Embodiment 1 at 2-8 hours was 221.3-227.4°C, the surface temperature of Embodiment 2 at 2-8 hours was 220.6-227.6°C, the surface temperature of Embodiment 3 at 2-8 hours was 221.9-227.8°C, and the surface temperature of Comparative Example 1 at 2-8 hours was 200.5-224.1°C. Compared with the embodiments, the initial temperature of Comparative Example 1 at 2 hours was lower, and the temperature rise after long-term heating was greater than that of the embodiments, and deformation occurred in Comparative Example 1 after continuous heating for 24 hours, indicating that after long-term heating, the temperature rise of Comparative Example 1 was large, resulting in material degradation after heating. Comparative Example 1 is a heating material for a commercially available automotive PTC heating pack. It can be seen that the heating material for a new energy automotive PTC heating pack prepared by the present invention has better electrothermal performance and thermal stability during long-term heating than commercially available products.
[0041] The surface temperature of Comparative Example 2 at 2-8h is 180.6-212.5°C, and the surface temperature of Comparative Example 3 at 2-8h is 163.6-192.4°C. The surface temperatures of Comparative Examples 2-3 are not as high as those of the embodiments. This is because Comparative Examples 2 and 3 did not perform the compounding of carbon nanotubes, iron ion solution and gallium-indium alloy, and their electrical conductivity is not as good as that of the embodiments. Therefore, the electric heating capacity is also reduced, resulting in a decrease in surface temperature. In addition, a certain degree of deformation occurs after 24h of continuous heating, indicating that the thermal stability of the material is not as good as that of the embodiments.
[0042] The surface temperature of Comparative Example 4 is 207.6-215.6°C at 2-8h, and the degree of deformation after 24h continuous heating is 7%, while the degree of deformation of Comparative Example 3 after 24h continuous heating is 8%. This is because salicylic acid can combine with gallium-indium alloy to form a gel, and in the absence of salicylic acid or gallium-indium alloy, the two cannot form a gel, resulting in degradation of the heating material after 24h continuous heating, reduced toughness, and difficulty in completely recovering to the original shape. Only when salicylic acid and gallium-indium alloy exist at the same time, the heating material has high toughness and high thermal stability after the combination of the two.
[0043] The surface temperature of Comparative Example 5 at 2-8h is 207-216.2°C, which is not as good as that of the embodiment, and deformation occurs after 24h of continuous heating, indicating that without adding acrylamide to assist emulsification to form a hydrogel fiber morphology, the heating performance, thermal stability and toughness of the prepared heating material are all lower than those of the embodiment.
[0044] The surface temperature of Comparative Example 6 at 2-8h is 211.5-244.9°C, and the surface temperature of Comparative Example 7 at 2-8h is 203.2-245.3°C. The surface temperature of Comparative Examples 6-7 at 2h is lower than that of the embodiment, but the increase is large at 8h, and a large degree of deformation occurs after continuous heating for 24h, with the deformation degree reaching 15% and 18%. It can be seen that after the carbon nanotube composite nanofluid is bonded to the surface of the polyester fabric through an acrylic emulsion, the thermal stability and toughness of the heating material can be significantly improved, while maintaining the temperature of the heating material stable, preventing the heating material from undergoing a significant degradation of material properties after long-term use, and increasing the initial temperature of the heating material, that is, the electrothermal performance is better.
[0045] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A preparation process of a heating material for a PTC heating pack of a new energy vehicle, characterized in that: The steps include: S1: Preparation of magnetic liquid metal carbon nanotubes The carboxylated multi-walled carbon nanotubes, FeCl3 solution and FeCl2 solution are mixed in a reaction bottle, heated to obtain a hot solution, sodium citrate aqueous solution is added dropwise to the hot solution, and allowed to stand for reaction to obtain an iron-compounded carbon nanotube suspension, the iron-compounded carbon nanotube suspension and gallium-indium alloy are mixed, ultrasonically treated to obtain a treated suspension, the treated suspension is allowed to stand, and magnetically separated to obtain magnetic liquid metal carbon nanotubes; S2: Preparation of carbon nanotube composite hydrogel fibers Add salicylic acid and acrylamide to deionized water, stir, then add crosslinking agent MBA, catalyst TEMED and initiator APS to obtain a mixed solution, add magnetic liquid metal carbon nanotubes to the mixed solution, polymerize, and obtain carbon nanotube composite hydrogel fibers; S3: Preparation of carbon nanotube composite nanofluids Weighing deionized water, heating, and magnetically stirring, adding carbon nanotube composite hydrogel fibers to the deionized water during magnetic stirring, and then adding graphene and anionic surfactant thereto to obtain a carbon nanotube composite nanofluid; S4: Preparation of heating materials for PTC heating packs in new energy vehicles Polyester fabric is selected as the base fabric, acrylic emulsion is evenly coated on the surface of the polyester fabric, and then dried. Then, carbon nanotube composite nanofluid is coated on the surface and dried to obtain a heating material for a PTC heating pack of a new energy vehicle.
2. The preparation process of a heating material for a PTC heating pack for a new energy vehicle according to claim 1, characterized in that: Step S1 is to prepare magnetic liquid metal carbon nanotubes, comprising the following steps: S1.1: 0.5-1 parts by mass of carboxylated multi-walled carbon nanotubes, 6-10 parts by volume of 0.1M FeCl3 solution and 3-6 parts by volume of 0.05M FeCl2 solution are mixed in a reaction flask, and then 5-10% by mass of ammonia water is added dropwise to the reaction flask until the pH value in the reaction flask is 8-9, heated to 80-85°C, and stirred for reaction for 30-35 minutes to obtain a hot solution; S1.2: Add 2-5 parts by volume of sodium citrate aqueous solution dropwise to the hot solution, maintain the reaction temperature at 60-65° C., and allow the reaction to stand for 1.5-2 hours to obtain an iron-complexed carbon nanotube suspension; S1.3: 0.02-0.04 parts by weight of the iron-compounded carbon nanotube suspension and 0.1-0.2 parts by weight of the gallium-indium alloy are mixed, and then cooled to 0-4° C. in an ice water bath, and subjected to ultrasonic treatment for 5-10 minutes to obtain a treated suspension; S1.4: The treated suspension is allowed to stand at 24-26°C, separated by magnetic attraction, the separated precipitate is dialyzed, washed with distilled water and anhydrous ethanol three times respectively, and vacuum dried to obtain magnetic liquid metal carbon nanotubes.
3. The preparation process of a heating material for a PTC heating pack of a new energy vehicle according to claim 2, characterized in that: Step S2 is to prepare carbon nanotube composite hydrogel fibers, comprising the following steps: S2.1: Add 0.4-0.5 parts by mass of salicylic acid and 3.6-4 parts by mass of acrylamide to 15-20 parts by mass of deionized water, stir magnetically for 1-1.5 hours, and after dissolution, add 1-2 parts by mass of crosslinker MBA, 0.5-1 parts by mass of catalyst TEMED and 2-3 parts by mass of initiator APS, stir at 800-1000 r / min for 10-20 minutes to obtain a mixed solution; S2.2: Add magnetic liquid metal carbon nanotubes to the mixed solution, the material-liquid ratio of magnetic liquid metal carbon nanotubes to the mixed solution is 1g: (0.5-0.8)L, and obtain a suspension. Inject the suspension into a polytetrafluoroethylene mold, polymerize at 24-26℃ for 6-7h, then take out and dry to obtain carbon nanotube composite hydrogel fibers.
4. The preparation process of a heating material for a PTC heating pack for a new energy vehicle according to claim 1, characterized in that: Step S3 is to prepare a carbon nanotube composite nanofluid, comprising the following steps: S3.1: Weigh 10-15 parts by weight of deionized water, heat to 60-70° C., and magnetically stir for 20-30 minutes. During the magnetic stirring, add 5-8 parts by weight of carbon nanotube composite hydrogel fibers to the deionized water; S3.2: Add 6-10 parts by mass of graphene and 1-3 parts by mass of anionic surfactant thereto, and stir for 5-10 minutes to obtain a carbon nanotube composite nanofluid.
5. The preparation process of a heating material for a PTC heating pack of a new energy vehicle according to claim 4, characterized in that: Step S4 prepares the heating material for the PTC heating pack of new energy vehicles, comprising the following steps: S4.1: Select a 20cm×20cm polyester fabric as the base fabric, insert the wire into the fabric in a spiral and serpentine manner, and evenly coat the surface of the polyester fabric with 16-24uL / cm 2 Acrylic emulsion, dried at 125-130℃ for 5-10min; S4.2: Then apply 0.04-0.06g / cm 2 The carbon nanotube composite nanofluid is applied on the surface and dried at 40-50° C. to obtain a heating material for a PTC heating pack of a new energy vehicle.
6. The preparation process of a heating material for a PTC heating pack of a new energy vehicle according to claim 2, characterized in that: In step S1.3, the mass proportion of gallium metal in the gallium-indium alloy is 75%, and the mass proportion of indium metal is 25%.
7. The preparation process of a heating material for a PTC heating pack of a new energy vehicle according to claim 4, characterized in that: The anionic surfactant in step S3.2 is specifically sodium dodecyl sulfate.
8. A heating material for a PTC heating pack for a new energy vehicle, which is prepared by the preparation process of the heating material for a PTC heating pack for a new energy vehicle according to any one of claims 1 to 7.